SAT0024 TRANSCRIPTOMIC PROFILING OF THE MICROENVIRONMENT DRIVEN RE-SHAPING OF PATHOGENIC CIRCULATORY AND SYNOVIAL HLA-DR+ CD4 T SUBSETS IN ACTIVE JUVENILE IDIOPATHIC ARTHRITIC PATIENTS. (June 2019) - Leong, Jing yao; Kumar, Pavanish; Chen, Phyllis; Yeo, Joo Guan; Chua, Camillus; Hazirah, Sharifah Nur; Arkachaisri, Thaschawee; Consolaro, Alessandro; Gattorno, Marco; Martini, Alberto; Albani, Salvatore
Abstract : Background: We have previously identified two pathogenic circulatory CD4 subsets in both Teff (CPLs)1 and Treg (iaTreg) 2 compartments of JIA patients that are HLA-DR +, antigen experienced, pro-inflammatory, correlating positively with disease activity and possessing strong synovial TCR sequence coverage. Despite being two functionally discordant T cell subsets (Teff/Treg), their immuno-phenotype and association with clinical fate suggests that these subsets may originate from a common precursor. Objectives: We seek to understand how the microenvironment could potentially influence and drive these subsets (CPLs/iaTregs) towards their pathological state. In an attempt to elucidate the common pathological gene drivers, we decided to perform next-generation RNA sequencing on sorted CPLs/iaTregs and conventional Teff/Treg counterparts in both circulation and synovium. Methods: CPLs were sorted as CD3 + CD4 + CD14 - HLADR + CD25/CD127 Teff gate, and iaTregs were sorted as CD3 + CD4 + CD14 - HLADR + CD25 hi /CD127 low Treg gate with FACs Aria II from n=16 active JIA PBMCs, n=8 paired JIA SFMCs, and n=8 healthy paediatric PBMCs. As a comparative control, similar HLADR - counterparts were respectively sorted from the same patients. Sorted cells were lysed and extracted for RNA, and cDNA conversion/amplification were then carried out using SMART-seq v4. Libraries are prepared and multiplexed using Nextera XT DNA library preparation kit, and ran on the Illumina HiSeq High output platform. Results: Comparative differential gene expression (DEG) analysis within the circulatory compartment indicate transcriptomic convergence between CPLs/iaTreg and divergence away from conventional Teff/Treg pools. Circulatory CPLs/iaTregs exhibit (a) common pathway dysregulation in T cell signalling (IFN-g, PD1, CD28 costimulation), (b) restriction in TCR oligoclonality and (c) common transcription factor drivers (SPL1 and E2F1) within the gene regulatory network, suggesting a common driving source acting on these two disparate compartments. To understand how this convergence originate, we compared CPLs/iaTreg and conventional Teff/Treg subsets from (a) healthy circulatory PBMCs, (b) JIA circulatory PBMCs and (c) paired JIA synovium. There was a gradual increase in transcriptomic convergence between Teff/CPLs, Treg/iaTreg and CPLs/iaTreg across the spatial/disease continuum, that is paralleled by an antigenic convergence in shared TCR clonotypes in CPLs/iaTreg. In particular synovium CPLs/iaTreg reveal 7 common dysregulated pathways; MHC II antigen presentation, T cell costimulation, IFNg pathway, apoptosis, viral response, bacteria response and chemotaxis. Conclusion: Overall the data indicate immune-phenotypic convergence between CPLs/iaTregs, that is strengthen across disease/spatial states. These findings underscore a potential mechanistic role of the inflammatory microenvironment in shaping two functionally dichotomic populations, relevant to disease pathogenies and progression. References: [1] Spreafico R, et al. A circulating reservoir of pathogenic-like CD4+ T cells shares a genetic and phenotypic signature with the inflamed synovial micro-environment. Ann Rheum Dis75, 459-465 (2016). [2] Rossetti M, et al. TCR repertoire sequencing identifies synovial Treg cell clonotypes in the bloodstream during active inflammation in human arthritis. Ann Rheum Dis76, 435-441 (2017). Disclosure of Interests: Jing yao Leong: None declared, Pavanish Kumar: None declared, Phyllis Chen: None declared, Joo Guan Yeo: None declared, Camillus Chua: None declared, Sharifah Nur Hazirah: None declared, Thaschawee Arkachaisri Speakers bureau: Abbvie Pte, Ltd, Alessandro Consolaro: None declared, Marco Gattorno Grant/research support from: MG has received unrestricted grants from Sobi and Novartis, Alberto Martini: None declared, Salvatore Albani: None declared